KAJIAN PUSTAKA KOMPOSIT LIMBAH PLASTIK SEBAGAI PAVING BLOK PENGHASIL ENERGI BERKELANJUTAN TERINTEGRASI PIEZOELEKTRIK DAN PHOTOVOLTAIC (VIZO) - Farah Yuki Prasetyawati; M. Maulana Yusuf; Alvin Ichwannur Ridho; Afifah Harwanti; Yulianto Agung Rezeki; Sarwanto Sarwanto; Dewanto Harjunowibowo; Sri Budiawanti; Suharno Suharno; Yesiana Arimurti; Dwi Teguh Rahardjo (Jurnal Fisika : Fisika Sains dan Aplikasinya, 2022)
This work aims to improve pedestrian functions, improve the welfare of waste banks and scavengers, and fulfil electricity needs for the surrounding community towards Society 5.0. The method of writing is done with secondary data through the latest literature study. The literature study focused on the development of technology for processing plastic waste, photovoltaic (PV), and piezoelectric (PZT) and their use in road construction. The results of the discussion show the potential of plastic waste as a composite material for paving. Similarly, PV and PZT can be integrated together as a producer of renewable electrical energy. With this innovation, VIZO is expected to be able to reduce plastic waste and provide welfare for the community, scavengers, waste banks, and help local government energy-saving programs.